A novel integrated angioscope-laser system for atherosclerotic carotid artery occlusion: Feasibility and techniques - Zhang, Boqian; Zhang, Guiyun (Frontiers in Surgery, 2022)
Introduction: Atherosclerotic extracranial carotid artery stenosis accounts for about 20-30% of all strokes, which is one of the leading causes of adult morbidity and mortality. Although carotid endarterectomy (CEA) is still the mainly operational manner for atherosclerotic carotid artery stenosis/occlusion (ACAS/ACAO), and carotid angioplasty and stenting (CAS) have been used as an alternative, both CEA and CAS have limitations of their own, such as extensive invasiveness and in-stent restenosis. Methods: In this study we established a novel interventional system in vitro to take advantage of both CEA and CAS. Twenty consecutive carotid atherosclerotic plaques were harvested from the patients who underwent CEA. The plaques were randomized into two groups and inserted into the pruned and sutured descending aortas of the swine in vitro. The ZebraScope™ was modified with a protective device on its flexible tip, so that the plaque could be dissected from the wall of parent carotid artery and ablated completely without damage to the carotid artery. The holmium:YAG (Ho:YAG) and thulium fiber laser (TFL) generators were alternately used when needed. Results: All the carotid atherosclerotic plaques were completely ablated by Ho:YAG laser and/or TFL. The Ho:YAG laser was more effective for the atherosclerotic plaques with severe calcification, while the TFL was more suitable for those with moderate calcification. There were still some thermal injury spots on the inner wall of the parent carotid artery caused by the laser in the non-protected group B. In the protected group A, on the contrary, there was no even a thermal injury spot was found on the relevant location except for one sample. The difference of ablating duration was statistically significant between group A (36.5±4.79 min) and group B (63.4±6.55 min) (P<0.01). Conclusion: According to our knowledge, this is the first attempt to ablate carotid atherosclerotic plaques assisted by the ZebraScope™ in vitro. The protective and dissecting device on the tip of the angioscope makes it safe and visible when the ablation is performed to carotid atherosclerotic plaques. The Ho:YAG laser and TFL are effective and safe for ablating the plaque in vitro.